Evaluation of radiographic waste management in dental offices and radiology clinics of São Luís (MA) - Marcos André dos Santos da Silva; Oswaldo Serra dos Santos-Neto; Jefson Moraes Amorim; José Bauer (Revista Sul-Brasileira de Odontologia, 2013)
Lack of information continues to lead the professionals of various areas to contribute to environment degradation, and Dentistry is a potential source of contamination through chemical residues resulting from radiographic procedures. Objective: To evaluate the management of residues resulting from radiographic processing in dental radiology clinics and dental offices in São Luís – MA, Brazil. Material and methods: A semi-structured questionnaire was prepared with the aim of characterizing the behavior of professionals and their procedures for discarding the processing solutions (developer, fixer, and water) and radiographic packing materials. A sample of 100 individuals represented 7.8% of the total number of 1,281 dentists in the city of São Luís. Results: A total of 92% of the participants believed that radiographic effluents could cause damage to the environment. Concerning to the fixer discarding, 43% affirmed that they threw the solution directly through the sink, 36% diluted the fixer in water and threw it into the sink, 14% used a specialized company to discard it and 7% used other means. The developer was discarded as follows: 42% threw it down the sink, 36% diluted it in water before throwing it into the sink, 13% used a specialized company to discard it and 9% used other ways. Considering to the discarding of the packing of the radiographic films, 51% threw them into the trash and 49% used a specialized disposal company. Conclusion: Large portions of dentists do not discard radiographic processing residues and films correctly.